The Effect Of Initiator Composition, Temperature, And Time On Ester Polymerisation Process Of Palm Fatty Acid Distillate - Aidil Akbar; Bahruddin Bahruddin; Yelmida Yelmida (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2017)
Palm Fatty Acid Distillate (PFAD) as a byproduct of the processed of palm oil has great potential to be used as raw material for polyester synthesis. The purpose of this research is to study ester polymerisation from PFAD with the composition of initiator, time and temperature as the parameters. First, the esterification process was done by the reaction of PFAD and methanol that used sulfuric acid as catalyst. The reactant composition was 1:8 molar ratio, speed of stirrer at 150 rpm, and H2SO4 composition is 1% (w/w) PFAD with temperature at 70° C for 2 hours. The polymerisation process was done by the reaction of esterification stage product and mixed with benzoyl peroxide as initiator. The variation for this stage were the composition of benzoyl peroxide 1%, 5%,and 9% (w/w) of methyl ester, polymerisation time 4, 5 and 6 hours and polymerisation temperatures of 140, 150 and 160° C. The result showed that the esterification stage product was obtained methyl ester and GC-MS analysis showed that the purity of methyl esters is 90,1%. Polymerisation product that is obtained a polyester but still have vinyl group in the component of the product. Based on the results of polymerisation reaction of the end product, dark and thick and has a viscosity of 180-200 cp. Based on the test results of GC-MS the composition of the methyl ester was reduced from 27.67% to 5.62% as the product of polymerization process which mean that the methyl ester have been converted. The R2 in this study gained 0.9663 which means a significant and lack of fit value of 0.1341 which means insignificant then the variable had a p-value of 0,0002 for the model which it less than α = 0.05 with variables that had a significant impact on model.Key words: benzoyl peroxide, palm fatty acid distillate, polyester, synthesis